The Role of Nurses in the Implementation of Puskesmas Accreditation to Improve the Quality of Health Services in Morowali District - Muhamad Aswar; B. Resti Nurhayati; Suwandi Suwandi; Endang Wahyati Yustina (SOEPRA, 2021)
Abstract: The role of nurses as health workers working at a Health Center (Puskesmas) is to provide health services through public and individual health efforts. The health services giving by the nurses are expected to increase the quality of health services in order to provide optimal services to communities conducted in integrated, comprehensive, and sustainable manners. The objective of this study was to see the nurses’ role in implementing Health Center accreditation in the efforts of improving the health services at Morowali District. This study used a socio-legal study approach having with analytical-descriptive specifications. It used primary and secondary data. The primary data gathering technique was through interviews with respondents and resource persons. The respondents consisted of nurses who worked in the Morowali District Health Centers while the resource persons were the heads of the Health Centers. The secondary data were obtained through related literature studies The role of nurses and the Health Centers accreditation at Morowali District were then qualitatively analyzed.In the accrediation process as regulated by The Minister of Health’s Regulation Nr. 46 of 2015 on Accreditation and The Minister of Health’s Regulation Nr. 75 of 2014 on Health Centers there were three types of assessment instruments, namely management administration, public health care efforts, and individual health care efforts. The role of nurses in the accreditation covered the three instruments. The nurses here played an important role in improving the quality of health services as the goal of accreditation. The supporting factors of the nurses’ role in the accreditation process dealt with legislations and human resources while the inhibiting factors dealt with the availability of health resources, the workload of the Health Center’s workers, lack of facilities and infrastructure.Keywords: role of nurses, health services quality, accreditation Abstrak: Peran perawat sebagai salah satu tenaga kesehatan yang bekerja di puskesmas yang menyelenggarakan pelayanan kesehatan untuk peningkatan mutu pelayanan melalui upaya kesehatan masyarakat maupun upaya kesehatan perorangan. Pemberian pelayanan kesehatan yang dilakukan oleh perawat melalui upaya kesehatan tersebut diharapkan adanya peningkatan mutu pelayanan kesehatan guna memberikan pelayanan yang optimal kepada masyarakat yang dilaksanakan secara terpadu, menyeluruh, dan berkesinambungan. Tujuan penelitian adalah untuk mengetahui peran perawat dalam pelaksanaan akreditasi puskesmas untuk peningkatan mutu pelayanan kesehatan di Kabupaten Morowali.Penelitian ini merupakan penelitian yuridis sosiologis dengan spesifikasi penelitian bersifat deksriptif analitik. Penelitian ini menggunakan data primer dan data sekunder. Metode pengumpulan data primer melalui wawancara dengan responden dan narasumber. Responden terdiri dari perawat yang bekerja di wilayah Kerja Puskesmas Kabupaten Morowali, sedangkan narasumber adalah Kepala Puskesmas. Data sekunder diperoleh melalui studi pustaka yang berhubungan Peran perawat dan akreditasi puskesmas di Kabupaten Morowali selanjutnya dianalisis secara kualitatif.Dalam pelaksanaan akreditasi yang diselenggarakan oleh puskesmas sebagaimana di atur dalam Permenkes No 46 Tahun 2015 tentang Akreditasi, Permenkes No 75 Tahun 2014 tentang Puskemas terdapat tiga jenis yang menjadi instrumen penilaian yaitu administrasi manajemen, upaya kesehatan masyarakat, dan upaya kesehatan peroorangan. Peran perawat dalam pelaksanaan akreditasi pada ketiga instrumen tersebut yakni administrasi manajemen, upaya kesehatan masyarakat dan upaya kesehatan perorangan. Perawat dalam pelaksanaan akreditasi berperan dalam peningkatan mutu pelayanan kesehatan sebagaimana tujuan dari akreditasi. Faktor pendukung terhadap peran perawat dalam pelaksanaan akeditasi yaitu faktor Perundang-undangan, dan sumber daya manusia. Sedangkan faktor penghambat yaitu ketersediaan sumber daya kesehatan, beban kerja petugas puskesmas, sarana dan prasarana.Kata Kunci : Peran Perawat, mutu pelayanan kesehatan, Akreditasi